2015
DOI: 10.1016/j.memsci.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thin film Pd deposition on the hydrogen permeability of Pd 60 Cu 40 wt% alloy membranes

Abstract: Effects of thin film Pd deposition on the Hydrogen permeability of Pd 60 Cu 40 wt% alloy membranes, Journal of Membrane Science, http://dx. AbstractPd 60 Cu 40 wt% (Pd 47.3 Cu 52.7 at%) membranes were surface modified by depositing Pd thin films of three different thicknesses (~100, 800 and 1,400 nm) on to one side of a range of as-received Pd 60 Cu 40 wt% cold-rolled foils via magnetron sputtering. The hydrogen permeability of the membranes was then measured and compared to uncoated material. The Pd 60 Cu 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…A lot of researches have shown that the hydrogen solubility of FCC PdCu phase is much higher than that of BCC counterpart, which is due to the stronger binding of hydrogen at FCC PdCu phase. 20,34,38,55 As to the effect of grain boundary (GB) on hydrogen solubility at PdCu phases, however, there is not any report so far in the literature. The present rst principles calculation is therefore executed to have a comparative study of fundamental inuence of GB on hydrogen solubility of PdCu phases.…”
Section: Hydrogen Solubility At S3 Grain Boundary Of Pdcumentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of researches have shown that the hydrogen solubility of FCC PdCu phase is much higher than that of BCC counterpart, which is due to the stronger binding of hydrogen at FCC PdCu phase. 20,34,38,55 As to the effect of grain boundary (GB) on hydrogen solubility at PdCu phases, however, there is not any report so far in the literature. The present rst principles calculation is therefore executed to have a comparative study of fundamental inuence of GB on hydrogen solubility of PdCu phases.…”
Section: Hydrogen Solubility At S3 Grain Boundary Of Pdcumentioning
confidence: 99%
“…Interestingly, some experimental studies reveal that hydrogen diffusion in GB of nickel is much faster than that in bulks due to a lower activation energy, 3,6 whereas the hydrogen diffusivity in GB of aluminum and nickel with ne grains is smaller than that in the bulks. 7,10,11,13 As to hydrogen diffusion in PdCu membranes, the reported experimental results are mainly concentrated on the polycrystalline phases, [19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35]37,39 while the theoretical investigations are all related to single crystals. 17,23,36,38,[40][41][42] It is therefore of importance to nd out the effect of GB on hydrogen diffusion of PdCu by means of rst principles calculation.…”
Section: Hydrogen Diffusivity At S3 Grain Boundary Of Pdcumentioning
confidence: 99%
See 1 more Smart Citation
“…Eq. 1 has been derived from data presented in an earlier article with a greater degree of accuracy than previously reported [27] VTXRD experiments were performed on Foils 1 and 2 in the as-received state. Initially, Foil 1 was cycled under flowing helium at a pressure of 445 kPa throughout the VTXRD experiment for the purpose of determining the phase transition temperature in a hydrogen-free inert atmosphere.…”
Section: Initial Ex-situ Xrd and In-situ Vtxrd Analysesmentioning
confidence: 99%
“…It was previously reported [26] that depositing a Pd thin film onto one side of an FCC Pd 60 Cu 40 wt% alloy foil membrane had the effect of increasing hydrogen permeability when the coated surface was positioned on the relatively high hydrogen pressure feed side during rig testing. This improvement in hydrogen permeability has been attributed to the presence of the Pd-rich Pd-Cu FCC phase which is formed as a result of Cu interdiffusing out of the bulk Pd 60 Cu 40 wt% foil membrane and into the Pd thin film.…”
Section: Accepted Manuscriptmentioning
confidence: 99%